Calcium-Dependent Protein Kinase CPK21 Functions in Abiotic Stress Response in Arabidopsis thaliana - Franz, Sandra; Ehlert, Britta; Liese, Anja; Kurth, Joachim; Cazalé, Anne-Claire; Romeis, Tina (Molecular plant, 2011)
Calcium-dependent protein kinases （CDPKs） comprise a family of plant serine/threonine protein kinases in which the calcium sensing domain and the kinase effector domain are combined within one molecule. So far, a biological function in abiotic stress signaling has only been reported for few CDPK isoforms, whereas the underlying biochemical mechanism for these CDPKs is still mainly unknown. Here, we show that CPK21 from Arabidopsis thaliana is biochemically activated in vivo in response to hyperosmotic stress. Loss-of-function seedlings of cpk21 are more tolerant to hyperosmotic stress and mutant plants show increased stress responses with respect to marker gene expression and metabolite accumulation. In transgenic Arabidopsis complementation lines in the cpk21 mutant background, in which either CPK21 wildtype, or a full-length enzyme variant carrying an amino-acid substitution were stably expressed, stress responsitivity was restored by CPK21 but not with the kinase inactive variant. The biochemical characterization of in planta synthesized and purified CPK21 protein revealed that within the calcium-binding domain, N-terminal EF1- and EF2-motifs compared to C-terminal EF3- and EF4-motifs differ in their contribution to calcium-regulated kinase activity, suggesting a crucial role for the N-terminal EF-hand pair. Our data provide evidence for CPK21 contributing in abiotic stress signaling and suggest that the N-terminal EF-hand pair is a calcium-sensing determinant controlling specificity of CPK21 function.